Bureaucratic Birthdates: Chronometric Old Age as Resource and Liability in U.S. Refugee Resettlement - Seibel, Kimberly (Refuge: Canada's Journal on Refugees, 2016)
This article examines age in refugee resettlement by connecting it to the bureaucratic contexts in which refugees acquire and become categorized by birthdates found in their documents. Frequently used as an objective metric, chronometric age takes on new meaning in migration and determines access to work and welfare. This article traces the trajectory of age documents of refugees in a program for “seniors” (sixty and up) in Chicago, Illinois. Drawing upon anthropology and critical gerontology scholarship, I resituate chronometric age in the dynamic relationship between institutions and definitions of old age in the United States. My purpose is to call attention to the consequences of applying U.S. concepts of age to refugees with limited resources.